MODEL FOR ASSESSMENT THE MATHEMATICAL EXPECTATION SPEED OF FUEL CONSUMPTION BY MILITARY SUBUNITS OF THE ARMED FORCES OF UKRAINE - Городнов, В.П.; Ковальов, І.В.; Дружинін, В.С. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2023)
The study of the experience of conducting an anti-terrorist operation (ATO) and an operation of the United Forces (OUF) in the war against the Russian Federation allows us to conclude that today the use of modern means of fire damage in combination with new approaches to intelligence conducting has had a significant effect on increasing the intensity and speed of troops movement during hostilities.In such conditions, random (unforeseen) consumption of fuel may appear with a simultaneous sudden decrease in its reserves below the specified (acceptable) norms. An unexpected drop in fuel reserves in military equipment can be related to many factors and, as a result, create conditions that will not allow to perform tasks in the offensive, during the development of success and when solving other combat tasks in the next day of hostilities.In order to ensure the fulfillment of combat missions by units and subunits of the Armed Forces and to prevent the limitation of their combat capability in connection with an unforeseen shortage of fuel during the operation, there is a need to develop a mathematical model, the use of which in the future will allow to calculate the time after which the level of fuel reserves will decrease below the permissible norm, and in the dynamics of the work of the logistics headquarters, it contributes to the timely provision of the troops needs.In the article, for the first time, simple expressions were obtained for calculating the required sample volume of a random fuel consumption value in the UAF subunits and for the error of estimating the mathematical expectation of this value in the sample, which guarantees the fulfillment of the requirements for the accuracy of calculations with a sample size significantly smaller than the traditional one and without using the concepts of "confidence interval" and "confidence probability", and corresponds to the limited capabilities of the Ukraine Armed Forces subunits to collect statistics during hostilities.The developed model can be used for further development of mathematical tools for predicting possible fuel consumption, for predicting needs and for providing the troops with fuel up to the established standards in a timely manner.

Вивчення досвіду ведення антитерористичної операції та операції Об’єднаних сил у війні з Російською Федерацією дозволяє зробити висновок про те, що на сьогоднішній день застосування сучасних засобів вогневого ураження у поєднанні з новими підходами ведення розвідки істотно вплинуло на підвищення інтенсивності та швидкості переміщення військ в ході бойових дій. В таких умовах можуть з’являтися випадкові (непередбачені) витрати пального з одночасним раптовим зниженням його запасів нижче визначених (допустимих) норм. Непередбачене падіння запасів пального у військовій техніці може бути пов'язане з багатьма факторами і, як наслідок, створювати умови, що не дозволять виконувати завдання у наступі, під час розвитку успіху та при вирішенні інших бойових завдань у наступну добу бойових дій.З метою забезпечення виконання бойових завдань частинами та підрозділами ЗСУ та недопущення обмеження їх боєздатності у зв’язку із непередбаченою нестачею пального в ході операції, виникає необхідність у розробці математичної моделі, застосування якої у подальшому дозволить розраховувати час, після якого рівень запасів пального знизиться нижче за допустиму норму, і в динаміці роботи штабів логістики сприяє своєчасному забезпеченню потреб військ.У статті вперше отримані прості вирази для розрахунку необхідного обсягу вибірки випадкової величини швидкості витрати пального у підрозділі ЗСУ і для похибки оцінки математичного сподівання цієї величини у вибірці, що гарантує виконання вимог до точності розрахунків при обсягу вибірки істотно меншому, ніж традиційний і без використання понять "довірчий інтервал" і "довірча ймовірність", та відповідає обмеженим можливостям підрозділів ЗСУ зі збору статистики під час бойових дій. Розроблена модель може бути використана для подальших розробок математичних інструментів прогнозування можливих витрат пального, для передбачення потреб та для своєчасного забезпечення військ пальним до встановлених норм.
МОДЕЛЬ ОЦІНКИ МАТЕМАТИЧНОГО СПОДІВАННЯ ШВИДКОСТІ ВИТРАТИ ПАЛЬНОГО ПІДРОЗДІЛОМ ЗБРОЙНИХ СИЛ УКРАЇНИ
Keywords: випадкові витрати пального; середнє арифметичне випадкової величини; число спроб; обсяг вибірки; random fuel consumption; arithmetic mean of a random variable; number of attempts; sample size